"Core" RxLR effectors in phytopathogenic oomycetes: A promising way to breeding for durable resistance in plants?. Issue 1 (1st January 2021) - Chepsergon, Jane; Motaung, Thabiso E.; Moleleki, Lucy Novungayo
ABSTRACT: Phytopathogenic oomycetes are known to successfully infect their hosts due to their ability to secrete effector proteins. Of interest to many researchers are effectors with the N-terminal RxLR motif (Arginine-any amino acid-Leucine-Arginine). Owing to advances in genome sequencing, we can now comprehend the high level of diversity among oomycete effectors, and similarly, their conservation within and among species referred to here as "c ore" R xLR e ffectors (CREs). Currently, there is a considerable number of CREs that have been identified in oomycetes. Functional characterization of these CREs propose their virulence role with the potential of targeting central cellular processes that are conserved across diverse plant species. We reason that effectors that are highly conserved and recognized by the host, could be harnessed in engineering plants for durable as well as broad-spectrum resistance.